(untitled) (Baghdad Science Journal, 2025)
During of Experimental result of this work , we found that the change of electrical conductivity proprieties of tin dioxide with the change of gas concentration at temperatures 260oC and 360oC after treatment by photons rays have similar character after treatment isothermally. We found that intensive short duration impulse annealing during the fractions of a second leads to crystallization of the films and to the high values of its gas sensitivity.